The Role of Gender in Learning and Content Management: A Review from an Educational and Islamic Perspective - Zubaidah Zubaidah; Aam Amaliyah (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Gender issues in education, including Islamic education, remain an important issue because learning practices and educational content often reproduce gender bias and inequality. Although Islam normatively upholds the principles of justice and equality, in educational practice, there is still a gap between Islamic teachings and their implementation. Objective: This study aims to examine the concept of gender from an Islamic perspective and analyze its implementation in learning management and educational content. Method: This study uses a qualitative approach with a descriptive-analytical library research design. Data were collected through documentation techniques on the texts of the Qur'an and Hadith as well as relevant academic literature, then analyzed using content analysis. Result: Gender inequality in education is caused more by social constructs and partial religious interpretations than by Islamic teachings themselves. Gender-responsive learning management and the development of gender-sensitive educational content have been proven to be crucial in creating a fair and inclusive learning process. Conclusion: The integration of a gender perspective in Islamic education is a strategic step toward realizing an education that aligns with the values of justice and humanity. Contribution: This study strengthens the conceptual framework of gender-perspective Islamic education, serving as both an academic and practical reference for creating more inclusive and equitable education.